Analisis Mengenai Dampak Lingkungan (AMDAL) sebagai Instrumen Pencegahan Pencemaran dan Perusakan Lingkungan Hidup Yang Berakibat Perbuatan Tindak Pidana Lingkungan ditinjau dari Undang-Undang Cipta Kerja - Yofirsta, Rova; Danil, Elwi; Rembrandt, Rembrandt (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
Indonesia, endowed with abundant natural resources, bears a constitutional obligation to ensure a healthy environment for all citizens as mandated by Article 28H of the 1945 Constitution. However, the ongoing environmental crisis—characterized by ecosystem degradation and the impacts of global warming—demands stronger legal instruments for the prevention and control of environmental pollution and destruction. Environmental law plays a crucial role in this regard, particularly through the Environmental Impact Assessment (AMDAL), which has historically served as a preventive planning tool and a primary prerequisite for business licensing. Significant changes have emerged following the enactment of Law No. 11 of 2020 on Job Creation, which shifts the licensing framework from a permit-based to a risk-based approach. This shift has downgraded the status of AMDAL from a primary requirement to a supplementary one, raising concerns about the weakening of its preventive function. Moreover, the perceived relaxation of environmental criminal sanctions under the new law has sparked questions about the state’s commitment to constitutional mandates for environmental protection. These concerns are further compounded by the conditional unconstitutionality status of the Job Creation Law, creating uncertainty regarding the effectiveness of environmental law enforcement. This study employs a normative-juridical approach to analyze the regulatory changes introduced by the Job Creation Law and its implementing regulation, Government Regulation No. 22 of 2021, in comparison with the previous framework under Law No. 32 of 2009 on Environmental Protection and Management. The focus lies on examining the urgency and effectiveness of AMDAL as an instrument for controlling environmental degradation and pollution, as well as its implications for potential environmental criminal acts under the new legal regime. The findings of this study are expected to provide a deeper understanding of the impact of legislative changes on environmental protection in Indonesia and to identify legal gaps that may exacerbate the environmental crisis. The study aims to inform policymakers in striking a balance between economic development and sustainable environmental protection.